Ryan and Jimmy: and the well in Africa that brought them together - Shoveller, Herb. (Tonawanda, NY Kids Can Press, 2006)
A true story of friendship and compassion in which a simple wish to help others brings focus to the necessities that unite us all.
5 - 9
Keywords: Wells - Africa; Caring in children; International cooperation